Student services : a handbook for the profession - Schuh, John H., 1947-; Jones, Susan R., 1955-; Harper, Shaun R., 1975-; Komives, Susan R., 1946- (Jossey-Bass, 2011)
"Since it was first published, Student Services has become a classic reference in the field. In this edition, a new panel of student affairs scholars examines the student experience in higher education, the evolution of the role of student affairs professionals, and the philosophies, ethics, and theories that guide the practice of student affairs work. This new edition covers a broad range of relevant topics including legal issues, managing student affairs programs, leadership, conflict resolution, community development professionalism, and developing institutional partnerships. It also addresses the future of the practice"--Vydavatelská anotace
Rev. vyd.: Student services / Susan R. Komives, Dudley B. Woodard, Jr., and associates. 4th ed. c2003
Keywords: vysokoškolské studium -- Spojené státy americké; vysokoškolští studenti -- Spojené státy americké; vysoké školy -- Spojené státy americké; vysokoškolské poradenství -- Spojené státy americké; college study -- United States; college students -- United States; universities and colleges -- United States; counseling in higher education -- United States; příručky; handbooks, manuals, etc